Comparison of Post-Stroke Functional Recovery between Ischemic and Hemorrhagic Stroke Patients: A Prospective Cohort Study - Lubis, Sabrina Anggi; Novitri, Novitri; Rizal, Ahmad (Althea Medical Journal, 2017)
pathophysiologic mechanism that underlies each stroke type may give different outcome in post-stroke patients. This study aimed to compare the improvement of functional outcome between both types of stroke among stroke patients admitted to Dr. Hasan Sadikin General Hospital (RSHS).Methods: Consecutive sampling was carried out on first-ever stroke patients admitted to neurological inpatient unit of RSHS from September 2015 to October 2015. Functional recovery, measured by subtracting Canadian Neurological Scale (CNS) on day-8 and day-1 of admission, was compared among two subgroups and analyzed using Mann-Whitney U test. Baseline characteristics were collected and analyzed.Results: Total of thirteen stroke patients was included in this study: ten ischemic stroke and three hemorrhagic stroke patients. CNS score improvement between ischemic and hemorrhagic stroke patients was not significantly different. However, hemorrhagic stroke had higher score than ischemic stroke with 0.30 CNS score difference.Conclusions: CNS improvement between ischemic and hemorrhagic stroke was not significantly different. Â DOI:Â 10.15850/amj.v4n2.1069